Correlations of PM metrics with human respiratory system deposited PM mass determined from ambient particle size distributions and effective densities - Lin, Yue; Bahreini, Roya; Lee, Seung-Bok; Bae, Gwi-Nam; Jung, Heejung (TAYLOR & FRANCIS INC, 2020)
The size distribution and effective density of ambient particles were measured with and without using Catalytic Stripper (CS) at Riverside, CA in September 2015 and June 2016 to calculate time-dependent human respiratory system deposited particulate matter (hereafter referred to as PMRS) mass using composition dependent growth factors along with the lung deposition fraction reported by ICRP (1994). The particle active surface area, black carbon (BC) mass, particle number (PN), solid particle number (SPN), and suspended PM mass (from particle size distributions and effective densities) were also obtained to investigate correlations with PMRS. Non-refractory organic and inorganic mass measured by an aerosol mass spectrometer (mAMS) provided additional information in relation to PMRS vs. chemical nature of particles. Ambient particle size distributions showed strong diurnal variations during the sampling period. While the respiratory system deposited PM mass fraction (0.32-0.36) did not vary much with time, the PMRS followed the trend of suspended PM mass in the ambient air. The PMRS for the alveolar region was the highest (0.3-1.0 mu g/m(3)), followed by that for nasal region (0.16-0.83 mu g/m(3)), and that for tracheobronchial region (0.05-0.27 mu g/m(3)). They all peaked during noon to 6 PM and reached the lowest value near midnight. Suspended PM mass in the ambient air correlated best with PMRS, followed by mAMS measured organics, active surface area, and BC mass. It is also found that particle hygroscopicity did not significantly affect correlations between metrics and PMRS. Considering the accessibility and cost of these measurements, we propose particle active surface area and BC mass to be considered when evaluating/monitoring the adverse health effects caused by PM. Copyright (c) 2019 American Association for Aerosol Research